Pengaruh Jiwa Kewirausahaan, Dukungan Keluarga dan Akses Modal terhadap Keberlanjutan Usaha pada UMKM Ritel Tradisional di Kecamatan Wuluhan - Rosma Hani Febrianti; Fatimah, Feti; Nursaidah Nursaidah (Lembaga Pengembangan Kinerja Dosen, 2025)
The sustainability of traditional retail MSMEs (Micro, Small, and Medium Enterprises) has become a critical issue in maintaining local economic stability amid the growing pressure from modern retail chains and shifting consumer behavior. This study is motivated by the need to understand both internal and external factors that influence the resilience of micro-enterprises in semi-rural areas such as Wuluhan District. The purpose of this research is to analyze the influence of entrepreneurial spirit, family support, and access to capital on the sustainability of traditional retail MSMEs. A quantitative approach was employed using multiple linear regression analysis on data collected from 60 MSME actors selected through simple random sampling. The findings indicate that, simultaneously, the three variables have a significant impact on business sustainability. Partially, entrepreneurial spirit and access to capital were found to have significant effects, while family support did not show a statistically significant impact, although it remains socially relevant. These results highlight the importance of strengthening entrepreneurial character and improving access to financing as key strategies for sustaining traditional retail MSMEs in the long term.